Endodontic treatment of unusual central incisors - KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (LIPPINCOTT WILLIAMS & WILKINS, 2002)
This report presents an endodontic therapy in an unusual case of a patient who had wide crowns of both permanent maxillary central incisors. The right maxillary central incisor had two separate canals on a fused root and the left had a large root canal within one root.